Patient Perspectives on Advance Care Planning via a Patient Portal. (August 2019) - Jordan, Sarah R.; Brungardt, Adreanne; Phimphasone-Brady, Phoutdavone; Lum, Hillary D.
Background: Patient portals can offer patients an opportunity to engage in the advance care planning (ACP) process outside of clinical visits. Objective: To describe patient perspectives on use of patient portal-based ACP tools. Design: Interviews with patients who used portal-based ACP tools. The tools included an electronic Medical Durable Power of Attorney (MDPOA) form to designate a medical decision maker, a patient-centered educational web page, online messaging, and patient access to completed advance directives stored in the electronic health record (EHR). Setting: Regional health-care system with a common EHR. Measurements: Semistructured interviews with purposefully sampled patients who used the ACP tools. Questions explored motivations for using the tools and perceptions about how the tools fit into ACP. Analysis followed a grounded hermeneutic editing approach. Results: From 46 patients (mean age: 49, 63% female), 4 key themes emerged: (1) individualized explorations of the ACP tools, (2) personal initiation and engagement with ACP tools through the portal, (3) value of connecting ACP portal tools to clinical care, and (4) practicality of the ACP tools. Patients described benefits of communicating with health-care team members who referred them to online ACP tools, as well as having the electronic MDPOA form connected to clinical care. Conclusions: Patients considered the portal-based ACP tools to be practical and feasible to use within the scope of their own ACP experiences. Further study is needed to understand whether portal-based ACP tools increase the quality and quantity of ACP conversations and documentation that is available to inform medical decision-making.